They are inverses if f( (g(x)) = x
f((g(x)) = (1/2) (2x + 4) - 2 = x + 2 - 2 = x
so this proves that g(x) is the inverse of f(x)
the other inverse g((f(x)) should also be = x
Answer:
No, Ssa triangle always not have two solutions
Step-by-step explanation:
the solution can be one, two or there will be no dolution. So this statement is false.
Answer:
1/2,3/6,5/10,8/16
Step-by-step explanation:
they all equal 1/2
Im not sure if thats what it was asking but yea
Answer:
8. -6
Step-by-step explanation:
<span>The ordinate is three more than twice the abscissa
</span>Ordnate: y; Abscissa: x
y=3+2x
x=-1→y=3+2(-1)=3-2→y=1→(x,y)=(-1,1)
x=0→y=3+2(0)=3+0→y=3→(x,y)=(0,3)
x=-1/3→y=3+2(-1/3)=3-2/3=(3*3-2)/3=(9-2)/3→y=7/3→(x,y)=(-1/3,7/3)
Answer: Option <span>A) {(-1,1),(0,3),(-1/3,7/3)}</span>